Problematika Pelaksanaan Magang Bagi Mahasiswa PGSD Secara Daring Pada Mata Pelajaran Bahasa Indonesia Masa Pandemi di SD Sidomulyo 04 - Atrianing Yessi Wijayanti; Rahayu Pristiwati; Subyantoro Subyantoro (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2021)
Changes in the learning system have caused problems, one of which is the implementation of internships, which are usually carried out offline, now must be carried out online because the Covid-19 pandemic has not yet ended. The purpose of this study was to determine the implementation, obstacles and efforts made in online internship learning at SD Sidomulyo 04.This research method is descriptive qualitative by using survey method. This research was carried out at SD Sidomulyo 04, carried out in August 2021. The data to be obtained from this research were in the form of data on implementation, obstacles that arise and efforts to solve problems for interns at SD Sidomulyo 04. The primary data sources are informants who play a role in research. these are student interns, tutor teachers, principals, and students. In addition, secondary data sources are obtained from documents, and screenshots of the implementation of learning while online. Data collection techniques in this study using interview techniques, documentation and questionnaires. Meanwhile, the data analysis process in this study includes three things, including: 1) data reduction, 2) data presentation, 3) drawing conclusions or verification. The results of the research and discussion of this study explain the implementation of learning during the COVID-19 pandemic which is carried out based on regulations set by the government. The change in the learning system from offline to online learning also has an impact on the emergence of various problems. Problems are obstacles in implementing internships in online learning for PGSD students. The obstacles found were from students, teachers and apprentices. Furthermore, these obstacles are sought solutions as an effort to overcome existing problems or obstacles. Keywords: Internship Implementation, Online, Indonesian Language Learning